Analisis Faktor-Faktor Determinan Stress Kerja pada Pekerja ABK (Kapal Penumpang KM Lauser) - Athala Syarania Putri Yuda; Zufra Inayah (Peneliti.net, 2023)
Workers as sailors (Ship's Crew) are jobs that can cause work stress. Generally, workers (ABK) spend three to four months working on ships or sailing and live far from home or family, therefore crew members must establish close relationships between colleagues so that a sense of kinship arises that they feel like their own family, as for the factors this study is workload, interpersonal relationships, work environment and family factors. The purpose of this study was to analyze the factors related to work stress on crew members (KM Lauser Passenger Ship). The type of research used is quantitative research with analytic observation methods and cross sectional approaches. The sampling technique used simple random sampling with a total of 63 respondents, then the research was analyzed using the chi-square test and the instrument used a questionnaire. The results obtained from this study are that there is a significant relationship between workload and interpersonal relationships with work stress because the P-value is <0.05 and there is no significant relationship between work environment and family factors because the P-value is > 0.05 . Based on the analysis of the research data, the results show that there is a workload relationship and interpersonal relationships so that it is necessary to change co-workers while on guard at night and establish relationships, communicate openly with co-workers so as not to cause conflict between co-workers